PERANAN LABORATORIUM FORENSIK DALAM PEMBUKTIAN ALAT BUKTI TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA DI WILAYAH HUKUM KEPOLISIAN DAERAH RIAU - Wendy Efradot; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The more widespread development of narcotic crime in Indonesia is very alarming for the nation's future , especially in the province of Riau . Police Forensic Laboratory as a tool specifically assist the Indonesian National Police has the responsibility to carry out tasks that are critical to uncover everything that is associated with all types and kinds of narcotics wearer or anyone who pengedarnya . However, to obtain higher truths necessary tools are sophisticated and advanced , and of course all the costs that are not few in number .Keywords : Forensic Laboratory - Crime - Narcotics